IFFAS (International Federation of Foot & Ankle Societies) 2024 학술대회 보고서 - 김지연; 원성훈; 윤여권; 박재용; Jiyoun Kim; Sung Hun Won; Yeo Kwon Yoon; Jae Yong Park (대한족부족관절학회지, 2024)
The International Federation of Foot and Ankle Societies (IFFAS) is a global organization for foot and ankle societies, comprising the Asian Federation of Foot and Ankle Surgeons (AFFAS), the European Foot and Ankle Society (EFAS), the Latin American Federation of Medicine and Surgery of the Foot and Leg (FLAMECIPP), the North American Federation of Foot and Ankle Societies (NAFFAS), and the Southern Federation of Foot and Ankle Society. Since 2005, IFFAS has organized worldwide conferences every three years, starting in Naples, Italy. The 2020 conference in Chile was postponed to 2022 due to COVID-19 pandemic and became biennial with the founding of the Southern Federation. Consequently, the conference is set to take place in Seoul in 2024. IFFAS 2024 was the first global foot and ankle conference held post-pandemic and significant as the first IFFAS event in Asia since the 2011 conference was canceled because of the Great East Japan Earthquake. Under the theme "Meet the knowledge and beautifulness," the event was hosted in Seoul. The academic program included an AFFAS-hosted event on May 30, followed by the IFFAS-hosted conference from May 31 to June 1, with all events organized by the Korean Foot & Ankle Society (KFAS).